Experimental Design-Based Formulation Optimization of Fast Dissolving Oral Film of Caffeine - Dr. Prakash K. Soni (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Caffeine, generally used in the treatment of fatigue, drowsiness, and lack of mental alertness, requires a rapid onset of action on the central nervous system as a stimulant through its fast and effective drug delivery. It has a naturally bitter taste, which can severely impact patient compliance, so it needs to be masked, and palatability needs to be improved. Objective: The caffeine fast-dissolving oral film, formulated using the solvent casting technique, delivers a quick onset of action and an immediate therapeutic effect. Materials and Methods: The fast-dissolving oral film was optimized using a Box–Behnken design with three factors at three levels, where Polyox N80, Polyox N1105, and HPMC E5 served as independent variables, and the swelling index, adhesion time, mucoadhesive strength, along with cumulative percentage drug release, were considered response variables. Results: The optimized fast-dissolving oral film showed uniform thickness and drug content. It had a swelling index of 125.21%, adhesion time of 1.16 min, and mucoadhesive strength of 0.049N. The film showed an immediate release of 95.86% over 30 min. Conclusion: The caffeine fast-dissolving oral film, produced via the solvent casting technique, ensures a rapid onset and immediate action. The research aims to focus on formulating caffeine oral film possessing desired critical quality attributes, i.e., good physical properties, thickness, and film weight, tensile strength, and drug content uniformity. In addition, the proposed oral film formulation is expected to have a fast drug release profile, better ex vivo mucoadhesion time, and higher ex vivo drug permeation compared to the conventional formulation.